2021
DOI: 10.1186/s40360-021-00538-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro growth inhibitory activity of Medicines for Malaria Venture pathogen box compounds against Leishmania aethiopica

Abstract: Introduction Leishmania aethiopica (L. aethiopica) is responsible for different forms of cutaneous leishmaniasis (CL) in Ethiopia. Treatment heavily depends on limited drugs, together with drawbacks like toxicity and microbial resistance. The current research aimed to investigate in vitro growth inhibitory activity of Medicines for Malaria Ventures - Pathogen Box (MMV - PB) compounds against L. aethiopica clinical isolate. Methodology Four hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A previous study identified activity of this substance against Leishmania aethiopica . 61 Another study showed that this class of substance, which is a trisubstituted pyridine derivative, has activity against Sphaeropsis sapinea , a pathogenic fungus of conifers. 62 This data, together with the results of our study suggests that future works with trisubstituted pyridine derivatives may improve the options to treat fungal infections of plants and animals.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study identified activity of this substance against Leishmania aethiopica . 61 Another study showed that this class of substance, which is a trisubstituted pyridine derivative, has activity against Sphaeropsis sapinea , a pathogenic fungus of conifers. 62 This data, together with the results of our study suggests that future works with trisubstituted pyridine derivatives may improve the options to treat fungal infections of plants and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these models also reveal variation factors and potential biases, such as a low replication rate of amastigotes compared to promastigotes [32,33], the influence of the macrophage infection rate [34], and the variety of host cells used (primary cells or cell lines) [35]. Thus, although many studies show a correlation between the results obtained on in vitro promastigotes and (axenic) amastigotes [36][37][38][39][40][41], it seems important to take all these various factors and potential biases into account before implementing secondary screenings and interpreting them.…”
Section: Challenges Involved In Implementing Exploratory Screening To Identify In Vitro Hit Compounds Against Leishmaniamentioning
confidence: 99%